2004
DOI: 10.1007/s00467-004-1480-6
|View full text |Cite
|
Sign up to set email alerts
|

Intima-media thickness and arterial elasticity in hypertensive children: controlled study

Abstract: The objective of this cross-sectional controlled study was to evaluate the intima-media thickness (IMT) of the common carotid artery (cIMT) and superficial femoral artery (fIMT), as well as the elastic properties of the common carotid artery, in children with essential arterial hypertension. The study included 49 children with newly detected essential hypertension [mean age 14.5 (range 6-20) years] and 61 healthy normotensive children [mean age 13.5 (range 6-20) years]. The cIMT and fIMT were evaluated by ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
84
2
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(104 citation statements)
references
References 31 publications
9
84
2
3
Order By: Relevance
“…Previous reports have controlled for this confounding effect of obesity by adjusting for BMI with multiple regression or by analyzing overweight and normal weight subjects separately, when comparing cIMT in hypertensive and normotensive groups. [12][13][14][15][16][17] Results have been variable, with some investigators reporting an association between childhood primary hypertension and increased cIMT 13 and others failing to find such an effect, after adjusting for BMI. 14 -17 Relationship between cIMT and daytime SBP index.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have controlled for this confounding effect of obesity by adjusting for BMI with multiple regression or by analyzing overweight and normal weight subjects separately, when comparing cIMT in hypertensive and normotensive groups. [12][13][14][15][16][17] Results have been variable, with some investigators reporting an association between childhood primary hypertension and increased cIMT 13 and others failing to find such an effect, after adjusting for BMI. 14 -17 Relationship between cIMT and daytime SBP index.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Recent studies have investigated whether cIMT is also increased in childhood primary hypertension. [12][13][14][15][16][17] However, these reports have been confounded by the high proportion of hypertensive subjects with obesity, itself an independent risk factor for increased cIMT. 18 -22 Consequently, after adjusting for body mass index (BMI), previous studies have been inconsistent in showing increased cIMT in hypertensive children and have failed to demonstrate office blood pressure (BP) as an independent predictor of cIMT.…”
mentioning
confidence: 99%
“…Increased CIMT, one of the first signs of early atherosclerosis, is related to high blood pressure, dyslipidemia, hyper-homocysteinemia and microinflammation (19,20). Elevated serum concentrations of CRP is another marker used to stratify CV risk by reflecting chronic inflammation in adult and pediatric CKD and dialysis patients (9,(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Litwin et al, 7 in a study that included ambulatory blood pressure monitoring (ABPM), femoral and carotid IMT measurement, and assessments of biochemical parameters and vascular function in both normotensive and hypertensive subjects, found that vascular thickness was increased in hypertensive adolescents compared with controls and was associated with decreased vascular distensibility and elasticity. Vascular thickness correlated with systolic blood pressure and pulse pressure, as well as with some biochemical measures of cardiovascular risk, including homocysteine, highdensity lipoprotein, and apolipoprotein A1.…”
mentioning
confidence: 99%
“…6,7 Increased cIMT is well established as a correlate of atherosclerosis in adults, typically occurring in conjunction with other cardiovascular risk factors. 8,9 In prospective studies, increased cIMT has been associated with increased rates of coronary heart disease events, especially in individuals with higher blood pressure, dyslipidemia, and cigarette smoking.…”
mentioning
confidence: 99%